Effect of welding thermal cycles on the heat affected zone microstructure and toughness of multi-pass welded pipeline steels - Nuruddin, Ibrahim K. (Cranfield University, 2012)
This research is aimed at understanding the effect of thermal cycles on the metallurgical and microstructural characteristics of the heat affected zone of a multi-pass pipeline weld. Continuous Cooling Transformation (CCT) diagrams of the pipeline steel grades studied (X65, X70 and X100) were generated using a thermo mechanical simulator (Gleeble 3500) and 10 mm diameter by 100 mm length samples. The volume change during phase transformation was studied by a dilatometer, this is to understand the thermodynamics and kinetics of phase formation when subjected to such varying cooling rates. Samples were heated rapidly at a rate of 400°C/s and the cooling rates were varied between t8/5 of 5.34°C/s to 1000°C/s. The transformation lines were identified using the dilatometric data, metallographic analysis and the micro hardness of the heat treated samples. Two welding processes, submerged arc welding (SAW) and tandem Metal Inert Gas (MIG) Welding, with vastly different heat inputs were studied. An API-5L grades X65, X70 and X100 pipeline steels with a narrow groove bevel were experimented with both welding processes. The welding thermal cycles during multi-pass welding were recorded using thermocouples. The microstructural characteristics and metallurgical phase formation was studied and correlated with the fracture toughness behaviour as determined through the Crack Tip Opening Displacement (CTOD) tests on the welded specimens. It was observed that SAW process is more susceptible to generate undesirable martensite-austenite (M-A) phase which induce formation of localised brittle zones (LBZ) which can adversely affect the CTOD performance. Superimposition of the multiple thermal cycles, measured in-situ from the different welding processes on the derived CCTs, helped in understanding the mechanism of formation of localised brittle zones. Charpy impact samples were machined from the two X65 and X70 grades, for use in thermal simulation experiments using thermo mechanical simulator (Gleeble). The real thermal cycles recorded from the HAZ of the SAW were used for the thermal simulations, in terms of heating and cooling rates. This is to reproduce the microstructures of the welds HAZ in bulk on a charpy impact sample which was used for impact toughness testing, hardness and metallurgical characterisation. The three materials used were showing different response in terms of the applied thermal cycles and the corresponding toughness behaviours. The X65 (a) i.e. the seamless pipe was showing a complete loss of toughness when subjected to the single, double and triple thermal cycles, while the X65 (b), which is a TMCP material was showing excellent toughness in most cases when subjected to the same thermal cycles at different test temperatures. The X70 TMCP as well was showing a loss of toughness as compared to the X65 (b). From the continuous cooling transformation diagrams and the thermally simulated samples results it could be established that different materials subjected to similar thermal cycle can produce different metallurgical phases depending on the composition, processing route and the starting microstructure.
Keywords: Thermal simulations; Gleeble 3500; submerged arc welding; Tandem MIG welding; Continuous Cooling Transformation diagrams; Dilatometry; Phase transformations; Charpy impact toughness; CTOD